I like it when my partner holds my hand: development of the Responses and Attitudes to Support during Pain questionnaire (RASP) - Krahé, Charlotte; Paloyelis, Yannis; Sambo, Chiara F.; Fotopoulou, Aikaterini (Frontiers in Psychology, 2014)
Social support can have beneficial effects on psychological and physiological well-being. During acute bodily pain, however, the effects of social support on pain are mixed. This variability may be due to the multifaceted nature of both pain and social support, as well as individual differences. In this paper, we present the development, psychometric assessment, and initial validation of the first self-report measure designed to address this variability in the general population; the Responses and Attitudes to Support during Pain questionnaire (RASP). The RASP includes questions on social support from the romantic partner as well as healthcare professionals (HCPs) and addresses different types of social support and pain responses. The development and validation of the RASP comprised four studies. In Study 1, a preliminary RASP version was completed by 179 healthy individuals regarding any type of acute pain. In Study 2, the reduced RASP was completed by 256 women with experiences of menstrual pain. Principal component analysis indicated a 22-item solution with five underlying dimensions reflecting general partner support, emotional support from HCPs, anxiety in the context of HCPs, pain behaviors during partner support, and distraction by the partner. Construct validity was assessed using a measure of adult attachment style. The RASP showed good validity and test-retest reliability. In Study 3, the 5-factor model received initial support through confirmatory factor analysis in a new sample of 120 individuals with recent musculoskeletal pain. Study 4 provided additional validation of the RASP in a sample of 180 individuals responding in reference to acute back pain. Overall, the RASP is a valid and reliable measure for assessing individual differences in attitudes and responses to social support in relation to acute pain.